Estrés académico e ideación suicida en jóvenes universitarios de América Latina: Revisión Sistemática - Aldeán Pinzón, Camila Alejandra (2024)
Suicidal ideation has been considered for many years as a universal and social phenomenon that is maintained over time, it has generated great importance in the scientific community in the world, but even more so in the university population due to its high prevalence and great impact. In recent times, research has shown that the presence of certain risk factors plays an important role in the development of suicidal ideation, mainly due to academic stress. Faced with this problem, the present research aims to determine the scientific evidence of the influence of academic stress and suicidal ideation in university students in Latin America in the last 10 years, also seeking to identify and highlight the types of stressors and stages of suicidal ideation present in them. A non-experimental literature review of a descriptive and cross-sectional type was carried out with a mixed approach, taking into account a sample of 25 research articles using inclusion and exclusion criteria. The results obtained indicate that academic stress is present at a moderate level, while the prevalence of suicidal ideation is at a medium level in university students. Among the most common types of stressors are lack of time, family dysfunction, pressure for grades, among others; and in the most present stages of suicidal ideation are the desire to die, suicidal plan, suicidal idea without a certain method and suicidal idea with a certain method without planning. In conclusion, study variables have become a challenge in the academic and scientific field due to the increase in figures in the world, mainly in the university community